The risk factors of sodium, potassium intake, and physical activity on hypertension in the elderly. - Fivi Melva, Diana; Annisa, Yolanda; Putri Aulia, Arza (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction. Hypertension is one of classified diseases silent killers , lots of them found in the group age pre elderly and elderly compared to group age more young . This stuy aim For know characteristics respondent , relationship sodium intake , potassium intake and activity physique with elderly . Method. Case control design study matching with age and sex . The technique sample used non- probability sampling. The samples were 33 people for each group case and control . Data analysis used the Chi-Square test . Data of Sodium intake and potassium intake were obtained from interview with food recall , data of physique activity obtained with use GPAQ questionnaire . Results. This study showed that group case own category sodium intake more (75.8%), potassium intake category less (78.8%) and activity physique category less (84.8%) in comparison group control . There's a significantly relation between sodium intake (p=0.003, OR=5.46), activity physical (P=0.004, OR=5.95) with hypertension , and. There is not relation between potassium intake with hypertension (p=0.181, OR=2.4). Conclusion. There is a significantly relationship between sodium intake and physique activity with hypertension . Sufferer hypertension recommended For change pattern eat with limit consumption foods that are high in sodium, increase consumption food high in potassium and divide seniors who don't working / not strong work for still do activity physique currently like bicycle or walk 30 minutes / day for 3-5 days in a week .